Intra-European Marie Curie Fellowship - Keivanidis, Panagiotis E. (My University, 2026)
Intra-European Marie Curie Fellow, co-ordinating and managing project 'Delayed Luminescence Spectroscopy of Organic Photovoltaic Systems' (DELUMOPV). Grant agreement ID: 299657, http://cordis.europa.eu/result/rcn/155572_en.html. Host Institution: Fondazione Istituto Italiano di Tecnologia, Centre for Nanoscience and Technology/Politecnico di Milano, Milan (IT)
Keywords: Natural sciences